Relationship Between Child-Mother Secure Attachment Style and Violence in Adolescent Romantic Relationship - Zarra Janna Muhammad; Yulia Ayriza (Psychological Research and Intervention, 2020)
This study aimed to assess the correlation between the secure attachment style of child-mother and violence in adolescents’ romantic relationships. A quantitative approach with a correlational method is used in this research. The subject in this study were 408 adolescents aged 18-22 years who were in romantic relationships and lives in the Special Region of Yogyakarta. The data collection method used in this study is the questionnaire method with the instrument used are the IPVAS-R scale and IPPA-M scale. Both scales used convergent validity with correlations of 0,18-0,78. Then the two scales were re-validated by expert judgement. Reliability for the IPVAS-R was 0,76, and the IPPA-M was 0,87. The data analysis used a non-parametric correlation test. The research results showed a negative correlation between child-mother secure attachment style and dating violence with r=-0,221 and α= 0,000 (p0,01). The higher the secure attachment style between child and mother, the lower the violence in romantic relationships.